2014
DOI: 10.3846/13923730.2013.802720
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Investigation Into the Effects of Fibers on Bituminous Mixtures

Abstract: The growing need for high quality bituminous mixtures in road construction, rehabilitation and maintenance is currently satisfied by means of techniques to produce polymer-modified bitumen, or by the addition of additives to mixtures during in-plant mixing operations. A rigorous rheological approach in the study of the bitumen modification process enables researchers to rationally compare different modifying agents and to evaluate their relative efficiency for specific field applications. As far as additives a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…It has been found that carbon fiber can improve the electrical property of asphalt but compromise the mechanical performance of asphalt concrete while steel fiber improves the stability of asphalt [38,39]. Industry uses cellulose fiber to reduce binder drain off during the transportation of the mix from the plant to the construction site [40,41]. As cigarette butt filter is cellulose acetate based fiber, it can be a potential replacement of natural cellulose fiber used in stone mastic asphalt.…”
Section: Classification Of Bitumenmentioning
confidence: 99%
“…It has been found that carbon fiber can improve the electrical property of asphalt but compromise the mechanical performance of asphalt concrete while steel fiber improves the stability of asphalt [38,39]. Industry uses cellulose fiber to reduce binder drain off during the transportation of the mix from the plant to the construction site [40,41]. As cigarette butt filter is cellulose acetate based fiber, it can be a potential replacement of natural cellulose fiber used in stone mastic asphalt.…”
Section: Classification Of Bitumenmentioning
confidence: 99%
“…To prevent formation of lumps of filler and to obtain a homogeneous final mixture, we used a method previously developed by the authors [34][35] and summarized in the following steps:…”
Section: Figure 2: Gradation Of the Aggregates In Bituminous Mixturesmentioning
confidence: 99%
“…Furthermore, several researches showed that mixing, curing, and compaction procedures must be considered carefully due to their great influence on overall performance of mixture [12][13][14][15]. Previous studies on inclusion of fiber in hot asphalt mixtures presented several improvements in performance of mixtures such as dynamic modulus, moisture susceptibility, and permanent deformations [16][17][18][19]. Fibers in cold emulsion mixes provided lower values of Marshall Stability and dynamic modulus [19] and had limited improvement on workability, elastic stiffness, and indirect tensile strength performance of half-warm emulsion mixtures [20]; addition of fibers to foamed bitumen mixtures improved the ITS, rutting resistance, and Marshall Stability values [21].…”
Section: Introductionmentioning
confidence: 99%
“…Fibers in cold emulsion mixes provided lower values of Marshall Stability and dynamic modulus [19] and had limited improvement on workability, elastic stiffness, and indirect tensile strength performance of half-warm emulsion mixtures [20]; addition of fibers to foamed bitumen mixtures improved the ITS, rutting resistance, and Marshall Stability values [21]. Generally, fibers can affect the specific characteristics of mixtures such as moisture sensitivities, fatigue life, and dynamic modulus [16][17][18][19], but the application of various types of fibers beside other types of additives and fillers should be further studied. For this purpose, Portland cement ranging from 1 to 2.5% has been incorporated by previous researchers as an active filler to evaluate the mechanical performance and moisture sensitivity of mixtures [21][22][23].…”
Section: Introductionmentioning
confidence: 99%